2013
DOI: 10.4000/osb.1511
|View full text |Cite
|
Sign up to set email alerts
|

Women's and men’s career interruptions in Europe : the role of social policies1

Abstract: How do countries differ in the type and level of women's and men's labour-market participation around parenthood? What are the models of interruptions prevalent? What is their impact on subsequent participation and wages? How does this impact depend on duration, type and "gender" of interruptions? How such impact is connected to the different social policies offered? Drawing on existing comparative datasets and offering a synthesis of the main "facts" and arguments provided so far in the literature, this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Previous studies also show that there are sex differences in retirement intentions and behaviours (Albertsen et al 2007;Dahl et al 2003) and in the effect of macroeconomic factors on retirement decisions (Axelrad and McNamara 2017;Shuey and O'Rand 2004). Older female workers, for example, may have to work longer to be entitled to the same benefits as men, because they are more likely to have had interruptions in their working careers (Musumeci and Solera 2013). Therefore, we will consider possible sex differences when examining determinants of early work exit.…”
Section: Sex Differencesmentioning
confidence: 98%
“…Previous studies also show that there are sex differences in retirement intentions and behaviours (Albertsen et al 2007;Dahl et al 2003) and in the effect of macroeconomic factors on retirement decisions (Axelrad and McNamara 2017;Shuey and O'Rand 2004). Older female workers, for example, may have to work longer to be entitled to the same benefits as men, because they are more likely to have had interruptions in their working careers (Musumeci and Solera 2013). Therefore, we will consider possible sex differences when examining determinants of early work exit.…”
Section: Sex Differencesmentioning
confidence: 98%
“…In countries such as Italy and Spain, unemployment rates among immigrants are not much higher than those among natives, while the overwhelming majority of immigrants are employed at the bottom of the occupational ladder, mainly manual jobs in the secondary labour market (Bernardi et al, 2011;Reyneri and Fullin, 2011). Immigrant women are often pushed into the unskilled domestic care of elderly persons, because a family-based welfare regime devolved most of the care for the weak family members to the family and to the (often extra-legal) market (Musumeci and Solera, 2013).…”
Section: The Occupational Integration Of Immigrant Womenmentioning
confidence: 99%
“…this is consistent with the findings of the research on the so-called 'work-life conflict' that the strain of reconciling work and family is strong not only among women but also among men, especially if they have high-level jobs or are self-employed. Men increasingly want to be involved fathers, but this seems to clash with the demands of their jobs and with the perception that they can only shed the image and the expectation of the 'unconditional worker' by incurring strong career penalties (McGinnity & Calvert, 2009;Musumeci & Solera, 2013).…”
Section: Preference Theory Revisedmentioning
confidence: 99%
“…By favouring or not favouring some possible courses of actions, they also define normative models. Various studies have shown, in fact, that the relative contribution of aQ4 men and fathers increases in the presence of 'good' policies such as a large provision of subsidized high-quality childcare services and fully paid parental leaves with a specific quota reserved for fathers (Fagan & Norman 2013;Musumeci & Solera, 2013;Smith & Williams 2007), but their success also depends on their specific configuration and on the discourse around them: if family policies are framed in terms of supporting fertility, as in France, more than supporting gender equality, as in Scandinavian countries, the gender division of labour is more traditional and the work-life stress is higher (Crompton, 2006;pfau-effinger, 2005).…”
Section: Preference Theory Revisedmentioning
confidence: 99%
See 1 more Smart Citation